دراسة تحليلية لرواية "مواكب الأحرار" لنجيب الكيلاني في مقاومة الاستعمار - Muhammad Anwar Bin Ahmad; Amurul Hafiz Bin Ali; Ilham Ramadan; Mohd Yazid Bin Abdulmajid (IIUM Press, International Islamic University Malaysia, 2024)
Non-Indexed Publication